2012
DOI: 10.1002/jbm.a.34124
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion formation to hemostatic agents and its reduction with a sodium hyaluronate/carboxymethylcellulose adhesion barrier

Abstract: The impact of hemostatic agents on postoperative adhesion formation has not been well studied. We hypothesized that hemostatic agents would be a significant nidus for adhesion formation and that a resorbable barrier would effectively reduce adhesions to hemostatic agents. Four commercial hemostatic agents, each composed of a different biomaterial matrix, were implanted in female Sprague-Dawley rats, and adhesion formation was examined 7 days after surgery. In separate studies, the effects of serosal trauma (vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Alginate gel is a foreign body and may elicit an inflammatory response, leading to increased adhesion formation. However, this has not been demonstrated for HA/CMC powder and also seems unlikely for alginate gel, given the moderate foreign body response shown histologically and the almost absent inflammatory response found in previous studies 15,30 .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Alginate gel is a foreign body and may elicit an inflammatory response, leading to increased adhesion formation. However, this has not been demonstrated for HA/CMC powder and also seems unlikely for alginate gel, given the moderate foreign body response shown histologically and the almost absent inflammatory response found in previous studies 15,30 .…”
Section: Discussionmentioning
confidence: 78%
“…During this interval fibrous adhesions form and mesothelial healing is completed, which makes formation of new adhesions unlikely. HA/CMC‐based adhesion barrier, which is absorbed fully from the abdominal cavity within 30 days, showed efficacy within 5–7 days.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion barrier devices that are used to separate tissue surfaces and prevent adhesions are an increasingly accepted adjunct to abdominopelvic surgery. Many studies have shown the antiadhesive effect of HA-CMC in animal models, human abdominal surgery, human facial surgery, human esophageal surgery, human breast surgery and human craniotomy [ 15 - 22 ]. Among them, there were interesting studies on a novel antiadhesive film based on cross-linked carboxymethylcellulose and atorvastatin, with that of sodium hyaluronate-carboxymethylcellulose [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 Greenawalt et al (2012) showed a sodium hyaluronate/carboxymethylcellulose barrier used for hemostatic agents at the time of surgery presented effects on after surgery adhesions in these preclinical models. 21 They hypothesized that a resorbable barrier would effectively reduce the adhesions to hemostatic agents and that hemostatic agents would be a significant nidus for adhesion formation.…”
Section: Animal Modelmentioning
confidence: 99%